2010
DOI: 10.1172/jci43670
|View full text |Cite
|
Sign up to set email alerts
|

The FoxO3/type 2 deiodinase pathway is required for normal mouse myogenesis and muscle regeneration

Abstract: The active thyroid hormone 3,5,3′ triiodothyronine (T3) is a major regulator of skeletal muscle function. The deiodinase family of enzymes controls the tissue-specific activation and inactivation of the prohormone thyroxine (T4). Here we show that type 2 deiodinase (D2) is essential for normal mouse myogenesis and muscle regeneration. Indeed, D2-mediated increases in T3 were essential for the enhanced transcription of myogenic differentiation 1 (MyoD) and for execution of the myogenic program. Conversely, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(191 citation statements)
references
References 54 publications
15
174
1
1
Order By: Relevance
“…6A). This observation, along with previous studies indicating that FOXO3 interacts with the Dio2 gene (15), suggested that FOXO1 may be the key molecule mediating the effects of nutrient status and insulin signaling on Dio2. This suspicion was strengthened by the observation that there was synchronized FIGURE 4.…”
Section: Figure 2 Nutrient Availability Increases D2 Activity Via Trsupporting
confidence: 77%
See 2 more Smart Citations
“…6A). This observation, along with previous studies indicating that FOXO3 interacts with the Dio2 gene (15), suggested that FOXO1 may be the key molecule mediating the effects of nutrient status and insulin signaling on Dio2. This suspicion was strengthened by the observation that there was synchronized FIGURE 4.…”
Section: Figure 2 Nutrient Availability Increases D2 Activity Via Trsupporting
confidence: 77%
“…A functional FOXO3 binding site is located in the 5Ј-UTR of the human DIO2, positively regulating DIO2 expression in developing skeletal muscle (15). Although proteins in the FOXO family can potentially bind to the same DNA cis-elements, the FOXO1 binding site identified in the present studies is within the DIO2 promoter, close to the transcription start site.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Blocking D2 activity inhibits the differentiation of myoblasts into mature myotubes, which are kept in active proliferation phase. In vivo experiments mirror this requirement for an increase in intracellular T3 since the expression of T3-dependent genes is reduced in the muscle of D2KO mice, which also have an inadequate MyoD response to injury and a marked delay in muscle regeneration (64). These observations are very exciting, considering that the capacity to modulate the thyroid status of muscle precursors could be a valuable tool in designing cell-based therapies for patients with muscle disease.…”
Section: Deiodinases and Skeletal Musclementioning
confidence: 92%
“…During this process, thyroid hormones orchestrate a programmed sequence of cell death and proliferation during which many organs are remodeled or replaced. In this situation, T3 deficiency seems to promote proliferation of undifferentiated cells, whereas a decrease in D3 and an increase in D2 activity lead to differentiation (64). These changes in deiodinases are controlled by various developmental transcription factors that have just begun to be identified.…”
Section: Deiodinases and Cell Proliferationmentioning
confidence: 99%